2021
DOI: 10.1001/jamanetworkopen.2021.26306
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Alectinib vs Ceritinib in ALK-Positive Non–Small Cell Lung Cancer in Phase 2 Trials and in Real-world Data

Abstract: IMPORTANCE Quantitative assessment of bias from unmeasured confounding and missing data can help evaluate uncertainty in findings from indirect comparisons using real-world data (RWD).OBJECTIVE To compare the effectiveness of alectinib vs ceritinib in terms of overall survival (OS) in patients with ALK-positive, crizotinib-refractory, non-small cell lung cancer (NSCLC) and to assess the sensitivity of these findings to unmeasured confounding and missing data assumptions. DESIGN, SETTING, AND PARTICIPANTSThis c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…The recent approval of second and third-generation ALKIs has dramatically changed the treatment algorithm of ALK-translocated lung cancer. In the absence of head-to-head comparisons between next-generation ALKIs, any next-generation ALKI may be considered a valid option as first-line therapy ( 33 , 34 ). Our meta-analysis showed consistency among efficacy and safety outcomes, highlighting a class-effect improvement over control therapies.…”
Section: Discussionmentioning
confidence: 99%
“…The recent approval of second and third-generation ALKIs has dramatically changed the treatment algorithm of ALK-translocated lung cancer. In the absence of head-to-head comparisons between next-generation ALKIs, any next-generation ALKI may be considered a valid option as first-line therapy ( 33 , 34 ). Our meta-analysis showed consistency among efficacy and safety outcomes, highlighting a class-effect improvement over control therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple imputation by chained equations of ECOG PS scores was performed under MAR and MNAR, then where consistent with eligibility criteria for this study, patients with imputed ECOG PS > 1 were excluded, and the comparisons of interest executed 8 .…”
Section: Methodsmentioning
confidence: 99%
“…This analysis was used to assess the robustness of the study by estimating the E-value 8 , 9 , 32 . The E-value represents the minimum association of a hypothetical unmeasured confounder with treatment assignment and outcome of interest (OS) on the risk ratio (RR) scale to nullify our estimated HRs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the toxicity profile of ceritinib from ASCEND-4 and ASCEND-5 indicated a higher frequency of dose interruptions and modifications due to adverse events (AEs) compared to chemotherapy. Real-world data comparing ceritinib versus alectinib in ALK+NSCLC found that alectinib exposure was associated with longer OS compared with ceritinib in ALK+ NSCLC ( 72 ). The pharmacokinetic (PK) data from the ASCEND-8 study ( 71 ) led to the FDA approval of ceritinib 450 mg QD, administered with food.…”
Section: Alk Targeted Therapies In Nsclcmentioning
confidence: 99%